Kandungan Fraksi Serat Ransum Pellet Unggas Dengan Penggunaan Tepung Indigoferazollingeriana - Putri Jati; Triani Adelina; Dewi Ananda Mucra (State Islamic University of Sultan Syarif Kasim Riau, 2017)
This study aims to evaluation the effect of Indigofera zollingeriana flour utilization inpoultry pellet ration on the content of the fiber fraction ,namely : Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), Acid Detergent Lignin (ADL), hemicelluloses and cellulose. The experimental design used Completely Randomized Design(CRD),which consists of 4 treatments and 5 replicates. The treatments were the level of Indigofera zollingeriana flour utilization that were T0 = 0% Indigofera zollingeriana (control),T1 = 5% Indigofera zollingeriana, T2 =10% Indigofera zollingeriana, T3 = 15% Indigofera zollingeriana. The results showed that the Indigofera zollingeriana utilization had no significant effect (P>0.05) on the content of NDF, hemicellulose, cellulose but had significantly effect (P<0.05) to the content of ADF and highly significant effect (P<0.01) on the content of ADL. It was concluded that the use of 15% Indigofera zollingerian alowered the content ADF and ADL, unable to reduce the content fNDF and unable to increase the content of hemicellulose and cellulose.The use of 15% Indigofera zollingeriana is t h e b e s t 30.39% NDF; 9.42% ADF; 2.25% ADL; 20.98% hemicellulose and 4.53% cellulose.